حل مسائل البرمجة الهدفية الخطيه باستخدام المصفوفات - بشير, رشيد (University of Thi-Qar Journal of Science, 2008)
The classical method is one of the common important methods in the field of operation research to solve linear goal programmingproblems.This method represents the deviation variable as difference between two nonnegative variables in the objective function and the goals , The problems are then solved by using linear programming methods. The aim of this paper is to develop such method .The developed method MPS is used then to solve linear goal programming problems. It is found that MPS method is better than the classical method, since MPS method reduces the solution tables which makes the calculations easier and reduces the time required to solve the problems under study .